2012
DOI: 10.3233/jad-2012-111661
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pioglitazone Treatment Improves Learning and Attenuates Pathological Markers in a Mouse Model of Alzheimer's Disease

Abstract: Thiazolidinediones (TZDs) are agonists at peroxisome proliferator-activated gamma-type (PPAR-γ) receptors and are used clinically for the treatment of type 2 diabetes where they have been shown to reestablish insulin sensitivity, improve lipid profiles, and reduce inflammation. Recent work also suggests that TZDs may be beneficial in Alzheimer’s disease (AD), ameliorating cognitive decline early in the disease process. However, there have been only a few studies identifying mechanisms through which cognitive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 112 publications
(126 reference statements)
4
91
0
1
Order By: Relevance
“…However, subsequent studies using PPAR agonists in several AD mouse models had variable success in observing changes in A␤ levels. Several studies using various treatment paradigms with PPAR␥ agonists observed decreases in soluble A␤ species (45,46), plaques (47,48) or both (27,36,49,50), and others reported decreased intracellular A␤ (51,52). However, there were also cases where PPAR␥ agonists exhibited no measurable effect on A␤ pathology (53)(54)(55).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, subsequent studies using PPAR agonists in several AD mouse models had variable success in observing changes in A␤ levels. Several studies using various treatment paradigms with PPAR␥ agonists observed decreases in soluble A␤ species (45,46), plaques (47,48) or both (27,36,49,50), and others reported decreased intracellular A␤ (51,52). However, there were also cases where PPAR␥ agonists exhibited no measurable effect on A␤ pathology (53)(54)(55).…”
Section: Discussionmentioning
confidence: 87%
“…LXR (9, 13, 18, 20 -24) and PPAR␥ (27,36,46,48,50,52,55,59,60) agonists have been reported to ameliorate memory deficits using a variety of tests in a range of mouse models. It should be noted, however, that Nicolakakis et al (53), Masciopinto et al (59), and Papadopoulos et al (54) reported no behavioral improvements after treating mice with pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of PPARc agonists improved cognitive function, suppressed inflammation, and reduced amyloid levels in many mouse models of AD (Camacho et al 2004;Combs et al 2000;Sastre et al 2003;Searcy et al 2012). In a rat AD model, injection of both ciglitazone and ibuprofen or oral pioglitazone administration potently suppressed Ab-caused microglial inflammatory reactions .…”
Section: Proliferator-activated Receptor Gamma (Pparc) Agonistsmentioning
confidence: 97%
“…Neuroprotective effects of the PPARg agonists rosiglitazone, pioglitazone, and 15-deoxy-prostaglandin J 2 were reported in studies of animal models of ischemic stroke (Bordet et al, 2006;Culman et al, 2007). It was shown that long-term treatment with pioglitazone improved cognitive deficits and AD-related pathology in a mouse model of AD (Sato et al, 2011;Gupta and Gupta, 2012;Searcy et al, 2012;Xiang et al, 2012). Neuroprotective effects of PPAR agonists have also been demonstrated in experimental models of PD (Chaturvedi and Beal, 2008;Ridder and Schwaninger, 2012).…”
mentioning
confidence: 90%